Food Additives: Foodborne Titanium Dioxide Nanoparticles Induce Stronger Adverse Effects in Obese Mice than Non‐Obese Mice: Gut Microbiota Dysbiosis, Colonic Inflammation, and Proteome Alterations (Small 36/2020). Issue 36 (10th September 2020) - Cao, Xiaoqiong; Han, Yanhui; Gu, Min; Du, Hengjun; Song, Mingyue; Zhu, Xiaoai; Ma, Gaoxing; Pan, Che; Wang, Weicang; Zhao, Ermin; Goulette, Timothy; Yuan, Biao; et al.
Abstract : In article number 2001858, Hang Xiao and co‐workers study how oral consumption of food additive TiO2 (E171, 112 nm) or TiO2 nanoparticles (NPs) (33 nm) leads to a series of adverse effects in mice, such as gut microbiota dysbiosis, colonic inflammation, and altered hepatic and colonic proteome. Importantly, TiO2 NPs produce stronger adverse effects than TiO2 (E171), and obese mice are more susceptible to these effects.